RESULTS OF INSTRUMENTAL STUDIES OF THE THYROID GLAND CONDITION IN DISEASED DOGS WITH HYPOTHYROIDISM AT THE BACKGROUND OF OBESITY - Lokes-Krupka, T. P.; Tsvilichovsky, M. I.; Kanivets, N. S.; Karysheva, L. P.; Burda, T. L. (Scientific Progress & Innovations, 2021)
The article presents the results of ultrasonography studies of the thyroid gland in domestic dogs suffering from hypothyroidism, and also differentiation depending on the degree of fleshing has been made. The re-search was conducted during 2018–2020 on the basis of veterinary clinics in Poltava and Kharkiv. During this time, 11 domestic dogs were examined, in which hypothyroidism was diagnosed during complex exami-nation. These animals belonged to different breeds, had different sex and age. Depending on the degree of fleshing, the animals were divided into two experimental groups. The first group of animals had normal fleshing; the second one had a clinical symptom of obesity. After analyzing the obtained results, we regis-tered more significant changes in the structure of the thyroid gland in dogs suffering from hypothyroidism in the first experimental group as compared with dogs with hypothyroidism at the background of obesity symp-toms (the second experimental group). This was a 100 % increase in the gland echogenicity, a decrease in its size, uneven contours, as well as thickening of the organ capsule in 75 % of animals. A characteristic struc-tural feature during ultrasonography of the thyroid gland in dogs with hypothyroidism at the background of obesity symptoms, was the presence of excessive amount of subcutaneous tissue in the study area, which sig-nificantly complicated the interpretation of the results. In these dogs only inhomogeneity of structure with the centers of the increased acoustic density was registered. More than half of the diseased dogs in the sec-ond group had decreased size of the gland; in the rest animals, the size of the organ did not change. It should be noted that a significant number of animals had an increase in the gland echogenicity, and the thickening of its capsule was found in less than half of the dogs in this group. The heterogeneity of the pancreas struc-ture was common to all dogs suffering from hypothyroidism, regardless of the presence or absence of obesi-ty,. Increased echogenicity, decreased size of the thyroid gland, uneven contours and thickening of the cap-sule were more often visualized at hypothyroidism of dogs with normal fleshing. The latter may be due to the presence of excessive amount of subcutaneous tissue in the examination area of obese dogs.